Knowledge of Hygienic Practices among the Kitchen Staff in Second Cycle Institutions in Kumasi - Commey, Vida; Margaret, Asamoah; Adwoa J, Hagan (Advances in Social Sciences Research Journal, 2017)
This study examined food safety practices among the kitchen staff in second cycle institutions in the Kumasi metropolis and aimed at evaluating the knowledge and attitudes of matrons, cooks and pantry hands in second cycle institutions on hygienic practices, and their perspectives on the effect of individual hygiene on food contamination. The researchers employed a mixed methodology as the research design—using questionnaire and in-depth interviews as instruments to collect data from kitchen staff members of Opoku Ware and St. Louis Girls’ Senior High Schools. The study found that, even though about 62% of the respondents have had no formal training in food safety practices prior to their recruitment, they however consider training as very crucial to the work of food preparation, food handling, as well as methods and processes of food preservation. As a result, they appreciate the need for constant training and workshops, and are as well prepared to participate in such trainings to build upon their knowledge on food safety and hygienic practices. The study also revealed that the kitchen staff members of the two institutions are conscious of personal hygiene and thus consider regular washing of hands with soap as one critical way of avoiding food contamination. The study, finally recommends periodic medical checks, in-service training on food handling and the use of protective clothing by staff in all schools to ensure food safety and hygienic practices in school kitchens.